2020
DOI: 10.3390/ani10122207
|View full text |Cite
|
Sign up to set email alerts
|

Semen Modulates Inflammation and Angiogenesis in the Reproductive Tract of Female Rabbits

Abstract: The maternal environment modulates immune responses to facilitate embryo development and ensure pregnancy. Unraveling this modulation could improve the livestock breeding systems. Here it is hypothesized that the exposure of the female rabbit reproductive tract to semen, as well as to early embryos, modulates inflammation and angiogenesis among different tissue segments. qPCR analysis of the gene expression changes of the anti-inflammatory interleukin-10 (IL10) and transforming growth factor beta family (TGFβ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Despite differences in seminal plasma composition and female genital anatomy, similar immunomodulatory effects were reported in various mammalian species, including humans, horses, sheep, rats, rabbits and mice. (Gardela et al, 2020;Portus et al, 2005;. However, although recent literature studies in this field reveal the immune modulation effect of SP in the female reproductive tract, studies indicating its effect on fertilisation success are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Despite differences in seminal plasma composition and female genital anatomy, similar immunomodulatory effects were reported in various mammalian species, including humans, horses, sheep, rats, rabbits and mice. (Gardela et al, 2020;Portus et al, 2005;. However, although recent literature studies in this field reveal the immune modulation effect of SP in the female reproductive tract, studies indicating its effect on fertilisation success are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Yousef et al also found that sperm bind to BOECs and stimulate the expression of IL10 and TGFB1 in BOECs [ 86 ], suggesting an induction of anti-inflammatory responses by sperm. However, the presence of sperm after natural mating decreases IL10 in the UTJ region of rabbit oviducts [ 87 ]. Bromfield et al show that the expression levels of Csf2 , Lif , and Il6 are similar between oviducts collected at the estrus stage or after mating with intact or vasectomized male mice [ 88 ].…”
Section: Progesterone Regulation Of Inflammation During Pregnancymentioning
confidence: 99%
“…Inflammation is a part of relevant steps of reproductive physiology, present during ovulation, mating, sperm tolerance, placentation, or parturition [7]. The role of semen and seminal plasma (SP) triggering temporary inflammation in the female reproductive tract has been demonstrated in most species [8], including human [9], mice [10], bovine [11], equine [12], porcine [13], and lagomorpha [14]. This temporal post-mating inflammation removes potential pathogens and exogenous SP-proteins, as well as the spermatozoa that do not reach the utero-tubal junction [15].…”
Section: Introductionmentioning
confidence: 99%